Pure rate effect on the concrete compressive strength in the split Hopkinson pressure bar test - Lee, Sangho; Kim, Kyoung-Min; Park, Jamin; Cho, Jae-Yeol (International journal of impact engineering, 2018)
•Strain acceleration and geometry of a specimen lead to inertia effects in SHPB test.•Concrete SHPB tests were performed.•DIF considering the pure rate effect was proposed.•Proposed DIF provided an accurate prediction for the apparent dynamic strength. The dynamic increase factor (DIF) has been widely used to consider the rate effect in the analysis and design of concrete structures that are subject to impact loads. A variety of DIFs have been proposed by many researchers based on the results of dynamic material tests such as the split Hopkinson pressure bar (SHPB) test. These DIFs have been adopted in authoritative design guidelines and model codes such as the ACI 349–13, ACI 370R-14, fib MC2010, and UFC 3-340-02. However, previous studies did not properly consider the strain acceleration and the geometrical characteristics of the test specimens that cause the axial and radial inertia forces which influence the test results. For this reason, predictions can become non conservative when these DIFs are used in the analysis and design of concrete structures that are subject to impact or impulsive loads. In this study, to overcome the limitations of existing DIFs, a new concrete DIF that excludes inertia effects by considering the strain acceleration and geometry of the specimens has been proposed based on SHPB test results. The proposed DIF was numerically validated using finite element analyses. Compared with other existing DIFs, the results show improved predictions of the enhancement of the concrete compressive strength due to rate effect.